Upscaling cassava processing machines and products in Liberia - Awoyale, W.; Asiedu, R.; Kawalawu, W.K.; Kolawole, P.; Diallo, T.A.; Edet, M.; Adetunji, M. (Faculty of Food Technology Osijek, 2020)
Cassava is produced by more than 80% of farming households and is an important contributor to gross domestic product (GDP) in Liberia. It is therefore important to assess the status of cassava processing into food and other products. A total of one hundred and sixty (160) well-structured questionnaires were used for the collection of information from eight counties, with twenty respondents from each county. It was found out that all the counties lack adequate modern cassava processing machines, with almost all cassava processing operations being done with rudimentary equipment. Gari and wet fufu are common products in Liberian markets, with no high-quality cassava flour (HQCF) or derivatives. Consequently, user and gender friendly processing machines were installed in six established modern cassava processing centres, and new cassava products, such as fufu powder, tapioca, and HQCF with its value-added products (10% bread and pastries), were introduced. This upscaling will enhance the cassava value chain in Liberia with improvement in livelihoods, especially for vulnerable women and unemployed youth.